Educação científica crítica e professores(as) de ciências: estudo sobre as contribuições da Ferramenta Avaliativa Ciência, Tecnologia e Sociedade (FACTS) para a formação docente - Marra, Nayara Nogueira Soares (2024)
Critical Scientific Education (CCE) is based on the complex thinking of Edgar Morin and STS studies and was built by Ibero-American researchers. CCE supported the creation of FACTS, a CTS Assessment Tool for educational processes and materials. FACTS has been disseminated to Natural Sciences teachers, including through in-service education courses, such as the one that contextualized this work. Our objective was to understand how an course based on FACTS can help in the construction of ECC-oriented discourses in in-service teachers. Specifically, we seek to: I) Characterize the spontaneous approach that professionals present in relation to FACTS at the beginning of the course; II) Verify the impacts of the course based on the content of the FACTS tool and the teaching discourse during and after the course. To meet these objectives, we produced data in three moments: a questionnaire on the initial approach of the course teachers towards FACTS, which was analyzed using the mean and relative mode; analysis of course meetings, through Discursive Textual Analysis; and semi-structured interviews to analyze teachers' speeches about their practice after training. The results indicated that, initially, the teachers approached the apprentice and advanced levels of FACTS. During continuing education, most interactions enabled connections between school and university. The main resistance/difficulties of teachers in relation to CCE are related to interdisciplinarity, technology conceptual aspects, and the traditional curriculum. Another challenge was the transposition of more abstract aspects - such as concepts and attitudes - to more concrete aspects, such as those associated with methodology and vice versa. After training, the analysis of the teachers' discourse about their teaching agency revealed that, even with environmental difficulties, there are behavioral and personal aspects that bring teachers closer to CCE. The first are a dialogical relationship with FACTS, reflection on one's own training and practice and the search for a human and anthropological conception to support professional practice. The personal characteristics aligned with CCE are self-reflection, dedication, critical sense, a relationship of pleasure with work and lucidity about professional responsibility. Considering the results of our work, we believe that metacognition, interdisciplinarity and attitudinal aspects can be useful for the training of teachers aligned with Critical Scientific Education.